Cytokines and immunoglobulin genetics in neonatal calf diarrhea - Fischer, Stephani Josepha; Justus Liebig University Giessen (My University, 2017)
The aim of the present dissertation was to improve the prognostic possibilities and therapeutic strategies in neonatal calf diarrhea. Thereby, new techniques in drug development should be established in the field of veterinary medicine.In the initial investigation, ten healthy Holstein Friesian calves were observed from birth until day 28 after birth, regarding their IL-6 gene expression in PBMCs and IL-6 serum concentrations. Additionally, IgA concentrations in serum and saliva, as well as IgG concentrations in serum were monitored. These immunoglobulins were chosen as representatives for the local (IgA in saliva) and the systemic (IgG in serum, IgA in serum) adaptive immunity. The milk fed to the calves could have been a possible source for all these three molecules and therefore was investigated, too. The aim of this initial study was to look into the physiological development of the immune system after birth with special emphasis to the development of IL-6. The data showed that calves were able to produce IL-6 by themselves directly after birth. However, IL-6, as well as IgA and IgG were present in the colostrum and therefore the uptake of colostrum contributed to serum concentrations in calves during the first days. Immunoglobulin A concentrations in saliva started to increase around day 7 after birth. At this time point IL-6 serum concentrations and IgA concentrations in saliva showed a significant positive correlation. At the following sampling time points, a positive correlation could not be observed between these two parameters. It was assumed that, unlike in mice, IL-6 does not have a linear influence on IgA concentrations in saliva, but is an important factor in the initialization of the IgA development (Ramsay et al., 1994). Further investigations under controlled conditions are needed to confirm these preliminary findings in the field. Referring to these findings, which confirmed IL-6 to be produced by calves even in the first days of life, the second study proved IL-6 as a prognostic marker in neonatal calf diarrhea. Twenty scouring calves were sampled two times, a first time at the beginning of diarrhea and a second time 7-10 days after the occurrence of symptoms. Data collected were clinical parameters, hematologic parameters, IL-6 serum concentrations and the diarrhea causing pathogen. For comparison, a control group of nine calves was sampled once to determine the IL-6 basis concentration in healthy calves. At the first sampling time point, the scouring calves showed significantly higher IL-6 serum concentrations than the control calves. Furthermore, calves developing a prolonged course of the disease had significantly higher IL-6 serum concentrations compared to calves that were clinically recovered after 7-10 days. Interleukin-6 was assumed as a useful prognostic tool in neonatal calf diarrhea, which could help to prevent fatal courses of the disease by the early detection of critical patients. As BRV and C. parvum were the only pathogens detected in these study, the assumption should be proven for the other main pathogens in neonatal calf diarrhea (e.g. E. coli (F5-ETEC), BCV).The third study of this dissertation aimed at developing a bovine antibody library as an innovative drug development strategy in veterinary medicine. As proof-of principle, a bovine scFv antibody against BCV should be screened from this library. In preparation of the antibody library, a bovine primer set was designed with the intention of being able to amplify the whole genomic immunoglobulin diversity in cattle. Therefore intensive research was done regarding bovine immunoglobulin genetics, including literature research and the author s own BLAST analyses. The designed primers were intensively tested for functionality before they were used in library construction. For the library construction, isolated PBMCs from a vaccinated Holstein Friesian bull served as basic material. The bull had been immunized with the dam vaccine Scourguard3 (Zoetis, Berlin, Germany) containing the antigens BCV, BRV and E. coli. The total RNA isolated out of these PBMCs was reverse transcribed in cDNA and antibody sequences were amplified by use of the established primer set. Antibody sequences were cloned into the phagemid pCANTAB5E and transformed in TG1 E. coli cells. Thereby, a library with a diversity of approximately 3x 109 individual clones was build. Phage display was used to screen this library for antibodies against BCV. After three panning rounds a specific scFv fragment was isolated and further tested for specificity and affinity. The scFv-SF-3E4 showed excellent binding kinetics (Km = 595 pM) and neutralization ability in cell culture until a concentration of 24 µg/ml. It was therefore considered to be an interesting candidate.
Zytokine und Immunglobulingenetik bei der neonatalen Diarrhoe des Kalbes
Keywords: neonatale Diarrhoe; Kalb; Zytokine; Immunglobuline; neonatle diarrhea; calf; cytokines; immunoglobulin; ddc:630